Perovskite solar cell of efficient hole transport layer without doped nickel chlorophyll derivative and preparation method of perovskite solar cell
By modifying natural chlorophyll-a, designing nickel chlorophyll derivatives and preparing hole transport layers through electrochemical polymerization, the problem of low power conversion efficiency of perovskite solar cells in the prior art is solved, and an efficient and stable perovskite solar cell is achieved.
Patent Information
- Application Number
- CN202411878244.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The power conversion efficiency of existing perovskite solar cells based on undoped chlorophyll materials is up to 19%, limiting their application in perovskite solar cells.
The hole transport layer of perovskite solar cells was prepared by electrochemical polymerization by electrochemical polymerization.
The energy conversion efficiency of perovskite solar cells is significantly improved, leading to the highest power conversion efficiency of 21.8%, and exhibits excellent stability and durability in long-term testing.
Smart Images

Figure CN119789667A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of perovskite solar cells (PSCs), and in particular to a perovskite solar cell with a high-efficiency hole transport layer without doping nickel chlorophyll derivatives and a preparation method thereof. Background Art
[0002] Among the emerging photovoltaic technologies, perovskite solar cells have attracted widespread attention due to their rapidly increasing energy conversion efficiency. To date, the highest energy conversion efficiency of perovskite solar cells has exceeded 26%. Among them, inverted perovskite solar cells have attracted much attention due to their advantages such as low hysteresis effect of current-voltage curve, good stability and low manufacturing cost. The hole transport layer plays a key role in improving the efficiency and stability of perovskite solar cells. Therefore, in order to improve the repeatability and service life of the device, it is crucial to develop high-performance undoped hole transport materials.
[0003] Chlorophyll (Chl) and its structurally related compounds are widely present in nature and have unique photoelectric properties, so people use them as hole transport materials for perovskite solar cells. For example, Chinese patent document CN116828941A discloses a perovskite solar cell based on an electropolymerized chlorophyll hole transport layer and a preparation method thereof, and a high-efficiency perovskite solar cell using an electrochemically polymerized chlorophyll film prepared by electrochemically polymerizing chlorophyll containing unsaturated bonds as a hole transport layer, and its photoelectric conversion efficiency can be as high as 19.0%. However, the current research based on undoped chlorophyll materials is still limited, resulting in the power conversion efficiency (PCE) of perovskite solar cells being only 19% at most, which limits its application in perovskite solar cells. Summary of the invention
[0004] The present invention aims to solve the technical problems in the prior art and provide a perovskite solar cell with an efficient hole transport layer without doping nickel chlorophyll derivatives and a preparation method thereof. The present invention uses natural chlorophyll-a for modification, and designs the nickel chlorophyll (NiChl-Deoxo) without carbonyl group and nickel chlorophyll (NiChl-CN) containing dicyanovinyl group at C13 position, and prepares them as the hole transport layer of the perovskite solar cell by electrochemical polymerization. The obtained perovskite solar cell has high energy conversion efficiency and stability.
[0005] In order to solve the above technical problems, the technical solutions of the present invention are as follows:
[0006] A perovskite solar cell with an efficient hole transport layer without doping nickel chlorophyll derivatives, comprising, from bottom to top, a transparent conductive glass anode, a hole transport layer, a perovskite layer, an electron transport layer, a hole blocking layer and a metal cathode;
[0007] Characterized in that the hole transport layer is a polymerized chlorophyll film Poly(NiChl-Deoxo) or Poly(NiChl-CN);
[0008] The structural formulas of chlorophyll monomers NiChl-Deoxo and NiChl-CN are as follows:
[0009]
[0010] In the above technical solution, the hole transport layer is a polymerized chlorophyll film Poly (NiChl-Deoxo) or Poly (NiChl-CN) prepared by electrochemical polymerization.
[0011] In the above technical solution, the transparent conductive glass anode is made of indium tin oxide (ITO) material, and the perovskite layer is made of Cs 0.05 FA 0.85 MA 0.1 PbI3, the electron transport layer is C 60 , the hole blocking layer is Bathocuproine (BCP) and the metal cathode is silver (Ag).
[0012] In the above technical solution, the thickness of the hole transport layer is 8-12nm, the thickness of the perovskite layer is 540-560nm, the thickness of the electron transport layer is 20-25nm, the thickness of the hole blocking layer is 6-8nm, and the thickness of the metal cathode is 50-70nm.
[0013] A method for preparing a perovskite solar cell with an efficient hole transport layer without a doped nickel chlorophyll derivative comprises the following steps:
[0014] 1) Pre-treating the transparent conductive glass anode with ultraviolet ozone;
[0015] 2) preparing a hole transport layer on the transparent conductive glass;
[0016] 3) Spin coating a perovskite layer on the hole transport layer;
[0017] 4) evaporating an electron transport layer, a hole blocking layer and a metal cathode on the perovskite layer;
[0018] It is characterized in that the step 2) comprises the following steps:
[0019] The hole transport layer is a polymerized chlorophyll film Poly (NiChl-Deoxo) or Poly (NiChl-CN) prepared by electrochemical polymerization;
[0020] A chlorophyll monomer NiChl-Deoxo or NiChl-CN solution is prepared as an electrolyte, and the hole transport layer is prepared by electrochemical deposition on the transparent conductive glass substrate obtained in step 1) using a potentiodynamic method.
[0021] In the above technical solution, the steps of preparing the chlorophyll monomer NiChl-Deoxo or NiChl-CN solution in step 2) are as follows:
[0022] The chlorophyll monomer NiChl-Deoxo or NiChl-CN and tetrabutylammonium hexafluorophosphate are dissolved in dichloromethane to obtain a chlorophyll monomer NiChl-Deoxo or NiChl-CN solution.
[0023] In the above technical solution, the mass volume ratio of the tetrabutylammonium hexafluorophosphate, the chlorophyll monomer and the dichloromethane is: 1g:8.5mg:25mL.
[0024] In the above technical solution, the step of preparing the hole transport layer by electrochemical deposition on the transparent conductive glass substrate obtained in step 1) using a potentiodynamic method in step 2) is as follows:
[0025] The transparent conductive glass substrate obtained in step 1) is placed in a three-electrode system as a working electrode, a platinum sheet is used as a counter electrode, an Ag / AgCl electrode is used as a reference electrode, and a chlorophyll monomer NiChl-Deoxo or NiChl-CN solution is used as an electrolyte. Cyclic voltammetry is used for electrochemical polymerization to prepare the hole transport layer.
[0026] In the above technical solution, the parameters of electrochemical polymerization are set as follows: maximum potential 1.3V, minimum potential 0V, starting potential 0V, scanning speed 100mV s -1 , the number of electrochemical cycles is 25.
[0027] In the above technical solution, after the polymerization is completed in step 2), the substrate is cleaned with dichloromethane and vacuum dried for later use.
[0028] The beneficial effects of the present invention are:
[0029] The present invention adopts natural chlorophyll-a for modification, and designs the C13 position to be nickel chlorophyll (NiChl-Deoxo) without carbonyl group and nickel chlorophyll (NiChl-CN) containing dicyanovinyl group, and prepares them as hole transport layer of perovskite solar cell by electrochemical polymerization method. The obtained perovskite solar cell has high energy conversion efficiency and stability.
[0030] The present invention uses an undoped nickel chlorophyll derivative as a hole transport layer to significantly improve the energy conversion efficiency of perovskite solar cells, achieving a maximum power conversion efficiency (PCE) of 21.8%, which is the highest reported value based on chlorophyll materials to date. The perovskite solar cell of the present invention exhibits excellent stability under long-term testing. After 2,600 hours of environmental exposure testing, the device can still maintain 95% of its initial efficiency, showing good durability and reliability, and is suitable for long-term use.
[0031] The method for preparing a perovskite solar cell based on an electropolymerized chlorophyll hole transport layer of the present invention has the advantages of a simple and easy synthesis process, low requirements on equipment, and good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0033] Figure 1 It is a structural diagram of a high-efficiency perovskite solar cell device based on undoped nickel chlorophyll as a hole transport layer in the comparative examples and embodiments of the present invention.
[0034] Figure 2 It is a current-voltage (JV) curve of a high-efficiency perovskite solar cell device based on undoped nickel chlorophyll as a hole transport layer in the comparative example and the embodiment of the present invention. DETAILED DESCRIPTION
[0035] The present invention discloses a perovskite solar cell with an efficient hole transport layer without doping nickel chlorophyll derivatives, which comprises, from bottom to top, a transparent conductive glass anode, a hole transport layer, a perovskite layer, an electron transport layer, a hole blocking layer and a metal cathode; the hole transport layer is a polymerized chlorophyll film Poly (NiChl-Deoxo) or Poly (NiChl-CN), and the hole transport layer is prepared by electrochemical polymerization;
[0036] The structural formula of chlorophyll monomer NiChl-Deoxo or NiChl-CN is as follows:
[0037]
[0038] In the present invention, the chlorophyll monomer is a chlorophyll derivative containing an unsaturated bond, and the polymerized chlorophyll film prepared by electrochemical polymerization is defined as an electropolymerized chlorophyll film in which the configured chlorophyll monomer solution is used as an electrolyte and the chlorophyll film is prepared by electrochemical deposition on a substrate using a potentiodynamic method.
[0039] Preferably, the transparent conductive glass anode is made of indium tin oxide (ITO) material, and the perovskite layer is made of Cs 0.05 FA0.85 MA 0.1 PbI3, the electron transport layer is C 60 , the hole blocking layer is Bathocuproine (BCP) and the metal cathode is silver (Ag).
[0040] The present invention has no special requirements for the thickness of each layer of the perovskite solar cell, and the required thickness can be prepared according to actual needs. Preferably, the thickness of the hole transport layer is 8-12nm, the thickness of the perovskite layer is 540-560nm, the thickness of the electron transport layer is 20-25nm, the thickness of the hole blocking layer is 6-8nm, and the thickness of the metal cathode is 50-70nm.
[0041] The method for preparing a perovskite solar cell with an efficient hole transport layer without a doped nickel chlorophyll derivative of the present invention comprises the following steps:
[0042] 1) Pre-treating the transparent conductive glass anode with ultraviolet ozone;
[0043] 2) preparing a hole transport layer on the transparent conductive glass;
[0044] 3) Spin coating a perovskite layer on the hole transport layer;
[0045] 4) evaporating an electron transport layer, a hole blocking layer and a metal cathode on the perovskite layer;
[0046] The step 2) comprises the following steps:
[0047] The hole transport layer is a polymerized chlorophyll film Poly (NiChl-Deoxo) or Poly (NiChl-CN) prepared by electrochemical polymerization;
[0048] A chlorophyll monomer NiChl-Deoxo or NiChl-CN solution is prepared as an electrolyte, and the hole transport layer is prepared by electrochemical deposition on the transparent conductive glass substrate obtained in step 1) using a potentiodynamic method.
[0049] Preferably, a specific implementation of step 2) is:
[0050] Dissolving chlorophyll monomer NiChl-Deoxo or NiChl-CN and tetrabutylammonium hexafluorophosphate in dichloromethane to obtain a chlorophyll monomer solution;
[0051] The transparent conductive glass substrate obtained in step 1) is placed in a three-electrode system as a working electrode, a platinum sheet is used as a counter electrode, an Ag / AgCl electrode is used as a reference electrode, the above-prepared chlorophyll monomer solution is used as an electrolyte, and electrochemical polymerization is performed using cyclic voltammetry to prepare the hole transport layer.
[0052] Further preferably, the chlorophyll solution is obtained by dissolving 1 g of tetrabutylammonium hexafluorophosphate and 8.5 mg of chlorophyll monomer in 25 mL of dichloromethane.
[0053] Further preferably, the parameters of the electrochemical polymerization are set as follows: maximum potential 1.3 V, minimum potential 0 V, starting potential 0 V, scanning speed 100 mV s -1 , the number of electrochemical cycles is 25.
[0054] Further preferably, after the polymerization in step 2) is completed, the substrate is cleaned with dichloromethane and vacuum dried for later use.
[0055] A specific embodiment of the method for preparing a perovskite solar cell with an efficient hole transport layer without doping nickel chlorophyll derivatives of the present invention is:
[0056] 1) Treatment of transparent conductive glass anode:
[0057] The cleaned transparent conductive glass was subjected to UV-ozone pretreatment for 20 minutes;
[0058] 2) Preparation and treatment of hole transport layer:
[0059] The transparent conductive glass pretreated with UV ozone in step 1) was placed in a three-electrode system as the working electrode, with a platinum sheet as the counter electrode and an Ag / AgCl electrode as the reference electrode. The electrolyte was 1 g of tetrabutylammonium hexafluorophosphate and 8.5 mg of chlorophyll monomer dissolved in 25 mL of dichloromethane. The electrochemical polymerization was performed using cyclic voltammetry, and the parameters were set as follows: maximum potential 1.3 V, minimum potential 0 V, starting potential 0 V, and scan rate 100 mV s -1 , the number of electrochemical cycles was 25. After polymerization, the film was thoroughly rinsed with dichloromethane and vacuum dried for later use;
[0060] 3) Preparation of perovskite layer:
[0061] Place the device in step 2) in a glove box filled with argon gas, and spin-coat the perovskite precursor solution on the hole transport layer. The spin coating process is: first spin coating at a speed of 1000 rpm / min for 10 seconds, then increase to 5000 rpm / min and spin coating for 40 seconds. Add 250 microliters of chlorobenzene 5 seconds before the end of spin coating. After the spin coating is completed, place the device on a hot stage for annealing at a temperature of 100°C for 30 minutes. ;
[0062] 4) Preparation of electron transport layer, hole blocking layer and metal cathode:
[0063] Using vacuum evaporation coating machine at a pressure less than 6×10 -4Pa, the electron transport layer, hole blocking layer and metal cathode are evaporated on the perovskite layer, and the evaporation rate is
[0064] The perovskite precursor solution of the present invention is Cs 0.05 FA 0.85 MA 0.1 The preparation process of PbI3 solution is as follows:
[0065] In a nitrogen glove box, 19.5 mg of CsI, 219.3 mg of FAI, 23.8 mg of MAI, 12.66 mg of MACl and 760.7 mg of PbI2 (10% excess) were dissolved in 1 mL of a DMF / DMSO solution with a volume ratio of 4:1 and stirred at room temperature for 3 hours.
[0066] In order to have a deeper understanding of the present invention, the technical solution is clearly and completely described below in conjunction with the embodiments. However, the embodiments of the present invention are only for explaining the present invention rather than limiting the present invention. All other implementation cases obtained by those skilled in the art without making any creative work are within the scope of protection of the present invention.
[0067] The raw materials used in the following examples are all commercially available products.
[0068] Example
[0069] 1) The etched ITO was ultrasonically treated with ITO cleaning agent, deionized water, acetone, alcohol, and isopropanol for 30 minutes in sequence; the cleaned transparent conductive glass was pretreated with ultraviolet ozone for 20 minutes;
[0070] 2) Dissolve 1g of tetrabutylammonium hexafluorophosphate and 8.5mg of chlorophyll monomer NiChl-Deoxo or NiChl-CN in 25mL of dichloromethane to prepare the electrolyte required for electropolymerization of chlorophyll, and stir the electrolyte for 2 hours. Place the transparent conductive glass pretreated with UV ozone for 20 minutes as the working electrode in a three-electrode system, with a platinum sheet as the counter electrode and an Ag / AgCl electrode as the reference electrode. Cyclic voltammetry was used for electrochemical polymerization, and the parameters were set as follows: maximum potential 1.3V, minimum potential 0V, starting potential 0V, and scan rate 100mV s -1 The number of polymerization cycles was 25. After polymerization, the film was thoroughly rinsed with dichloromethane and vacuum dried for later use.
[0071] 3) Prepare Cs in an argon glove box 0.05 FA 0.85 MA 0.1PbI3 precursor solution, 19.5 mg of CsI, 219.3 mg of FAI, 23.8 mg of MAI, 12.66 mg of MACl and 760.7 mg of PbI2 (10% excess) were dissolved in 1 mL of DMF / DMSO solution with a volume ratio of 4:1, and stirred at room temperature for 3 hours. The substrate was sent to the glove box, and the perovskite precursor solution was spin-coated on the hole transport layer. The spin coating process was: first spin-coated at a speed of 1000 rpm / min for 10 seconds, then increased to 5000 rpm / min, and spin-coated for 40 seconds. 250 microliters of chlorobenzene were added 5 seconds before the end of spin coating. After the spin coating was completed, the substrate was placed on a hot stage for annealing at a temperature of 100°C for 30 minutes.
[0072] 4) Finally, the substrate is sent into the organic evaporation deposition machine. When the pressure in the chamber is lower than 6×10 -4 Pa evaporation electron transport layer C 60 , hole blocking layer Bathocuproine (BCP) and metal cathode silver, the evaporation rate of which is The silver film thickness is 60nm. Thus, a perovskite solar cell based on Poly(NiChl-Deoxo) and Poly(NiChl-CN) as the hole transport layer is obtained. The device structure is shown in Figure 1 As shown. In this embodiment, the thickness of the hole transport layer is 10nm, the thickness of the perovskite layer is 560nm, the thickness of the electron transport layer is 20nm, the thickness of the hole blocking layer is 6nm, and the thickness of the metal cathode is 60nm. The thickness of each layer can actually be any value within the aforementioned limited range, and only the preferred thickness value is given here.
[0073] Comparative Example
[0074] The hole transport layer material of this comparative example is chlorophyll (NiChl-Oxo) without substituent modification, and its C13 position is the carbonyl group of natural chlorophyll-a, which has not been treated. For comparison, the chlorophyll material is prepared into a polymerized chlorophyll film by electrochemical polymerization as the hole transport layer of the perovskite solar cell;
[0075] The structural formula of NiChl-Oxo is as follows:
[0076]
[0077] The specific steps include:
[0078] 1) The etched ITO was ultrasonically treated with ITO cleaning agent, deionized water, acetone, alcohol, and isopropanol for 30 minutes in sequence; the cleaned transparent conductive glass was pretreated with ultraviolet ozone for 20 minutes;
[0079] 2) Dissolve 1g of tetrabutylammonium hexafluorophosphate and 8.5mg of chlorophyll monomer NiChl-Oxo in 25mL of dichloromethane to prepare the electrolyte required for electropolymerization of chlorophyll, and stir the electrolyte for 2 hours. Place the transparent conductive glass pretreated with UV ozone for 20 minutes as the working electrode in a three-electrode system, with a platinum sheet as the counter electrode and an Ag / AgCl electrode as the reference electrode. Cyclic voltammetry was used for electrochemical polymerization, and the parameters were set as follows: maximum potential 1.3V, minimum potential 0V, starting potential 0V, and scan rate 100mV s -1 The number of polymerization cycles was 25. After polymerization, the film was thoroughly rinsed with dichloromethane and vacuum dried for later use.
[0080] 3) Prepare Cs in an argon glove box 0.05 FA 0.85 MA 0.1 PbI3 precursor solution, 19.5 mg of CsI, 219.3 mg of FAI, 23.8 mg of MAI, 12.66 mg of MACl and 760.7 mg of PbI2 (10% excess) were dissolved in 1 mL of DMF / DMSO solution with a volume ratio of 4:1, and stirred at room temperature for 3 hours. The substrate was sent to the glove box, and the perovskite precursor solution was spin-coated on the hole transport layer. The spin coating process was: first spin-coated at a speed of 1000 rpm / min for 10 seconds, then increased to 5000 rpm / min, and spin-coated for 40 seconds. 250 microliters of chlorobenzene were added 5 seconds before the end of spin coating. After the spin coating was completed, the substrate was placed on a hot stage for annealing at a temperature of 100°C for 30 minutes.
[0081] 4) Finally, the substrate is sent into the organic evaporation deposition machine. When the pressure in the chamber is lower than 6×10 -4 Pa evaporation electron transport layer C 60 , hole blocking layer Bathocuproine (BCP) and metal cathode silver, the evaporation rate of which is The silver film thickness is 60nm. Thus, a perovskite solar cell based on Poly (NiChl-Oxo) as a hole transport layer is obtained. The device structure is as follows Figure 1 As shown, the thickness of the hole transport layer is 10 nm, the thickness of the perovskite layer is 560 nm, the thickness of the electron transport layer is 20 nm, the thickness of the hole blocking layer is 6 nm, and the thickness of the metal cathode is 60 nm.
[0082] Table 1 shows the photovoltaic parameters of the perovskite solar cell devices prepared in the embodiments of the present invention and the comparative examples using Poly(NiChl-Oxo), Poly(NiChl-Deoxo) and Poly(NiChl-CN) as hole transport layers, respectively.
[0083] Table 1
[0084]
[0085] Figure 1 It is a structural diagram of a perovskite solar cell device based on Poly(NiChl-Oxo), Poly(NiChl-Deoxo) and Poly(NiChl-CN) as a hole transport layer prepared in the comparative examples and embodiments of the present invention.
[0086] Figure 2 The current-voltage (JV) curves of high-efficiency perovskite solar cell devices based on Poly(NiChl-Oxo), Poly(NiChl-Deoxo) and Poly(NiChl-CN) as hole transport layers in comparative examples and embodiments of the present invention correspond to Table 1. Compared with the perovskite solar cell with an electropolymerized chlorophyll hole transport layer (Poly(NiChl-Oxo)) not modified at the C13 position, the perovskite solar cell based on the electropolymerized chlorophyll hole transport layer (Poly(NiChl-Deoxo) and Poly(NiChl-CN)) modified with a substituent at the C13 position in the present invention achieves a significant improvement in photoelectric conversion efficiency, and the photoelectric conversion efficiency can reach 21.8%.
[0087] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A perovskite solar cell with an efficient hole transport layer without a nickel-doped chlorophyll derivative, comprising, from bottom to top: Transparent conductive glass anode, hole transport layer, perovskite layer, electron transport layer, hole blocking layer and metal cathode; Characterized in that the hole transport layer is a polymerized chlorophyll film Poly(NiChl-Deoxo) or Poly(NiChl-CN); The structural formulas of chlorophyll monomers NiChl-Deoxo and NiChl-CN are as follows:
2. The perovskite solar cell according to claim 1, characterized in that The hole transport layer is a polymerized chlorophyll film Poly (NiChl-Deoxo) or Poly (NiChl-CN) prepared by electrochemical polymerization.
3. The perovskite solar cell according to claim 1, characterized in that The transparent conductive glass anode is made of indium tin oxide (ITO) material, and the perovskite layer is made of Cs 0.05 FA 0.85 MA 0.1 PbI3, the electron transport layer is C 60 , the hole blocking layer is Bathocuproine (BCP) and the metal cathode is silver (Ag).
4. The perovskite solar cell according to claim 1, characterized in that: The thickness of the hole transport layer is 8-12 nm, the thickness of the perovskite layer is 540-560 nm, the thickness of the electron transport layer is 20-25 nm, the thickness of the hole blocking layer is 6-8 nm, and the thickness of the metal cathode is 50-70 nm.
5. A method for preparing a perovskite solar cell according to any one of claims 1 to 4, comprising the following steps: 1) Pre-treating the transparent conductive glass anode with ultraviolet ozone; 2) preparing a hole transport layer on the transparent conductive glass; 3) Spin coating a perovskite layer on the hole transport layer; 4) evaporating an electron transport layer, a hole blocking layer and a metal cathode on the perovskite layer; It is characterized in that the step 2) comprises the following steps: The hole transport layer is a polymerized chlorophyll film Poly (NiChl-Deoxo) or Poly (NiChl-CN) prepared by electrochemical polymerization; A chlorophyll monomer NiChl-Deoxo or NiChl-CN solution is prepared as an electrolyte, and the hole transport layer is prepared by electrochemical deposition on the transparent conductive glass substrate obtained in step 1) using a potentiodynamic method.
6. The preparation method according to claim 5, characterized in that: The steps of preparing the chlorophyll monomer NiChl-Deoxo or NiChl-CN solution in step 2) are as follows: The chlorophyll monomer NiChl-Deoxo or NiChl-CN and tetrabutylammonium hexafluorophosphate are dissolved in dichloromethane to obtain a chlorophyll monomer NiChl-Deoxo or NiChl-CN solution.
7. The preparation method according to claim 6, characterized in that: The mass volume ratio of the tetrabutylammonium hexafluorophosphate, the chlorophyll monomer and dichloromethane is: 1 g: 8.5 mg: 25 mL.
8. The preparation method according to claim 5, characterized in that: In step 2), the steps of preparing the hole transport layer by electrochemical deposition on the transparent conductive glass substrate obtained in step 1) using a potentiodynamic method are as follows: The transparent conductive glass substrate obtained in step 1) is placed in a three-electrode system as a working electrode, a platinum sheet is used as a counter electrode, an Ag / AgCl electrode is used as a reference electrode, and a chlorophyll monomer NiChl-Deoxo or NiChl-CN solution is used as an electrolyte. Cyclic voltammetry is used for electrochemical polymerization to prepare the hole transport layer.
9. The preparation method according to claim 8, characterized in that: The parameters of electrochemical polymerization were set as follows: maximum potential 1.3 V, minimum potential 0 V, starting potential 0 V, and scan rate 100 mV s -1 , the number of electrochemical cycles is 25.
10. The preparation method according to claim 5, characterized in that: Step 2) After the polymerization is completed, the substrate is cleaned with dichloromethane and vacuum dried for later use.
Citation Information
Patent Citations
Lead-free double perovskite solar cell and preparation method thereof
CN110993797A
Lead-free double perovskite solar cell and preparation method thereof
CN112563419A
CsPbCl3: Yb < 3 + > perovskite film modified by chlorophyll and preparation method and application of CsPbCl3: Yb < 3 + > perovskite film
CN116004229A
Perovskite / dye sensitized modified solar cell and preparation method thereof
CN116723710A
Perovskite solar cell based on electro-polymerization chlorophyll hole transport layer and preparation method thereof
CN116828941A